Implementing Knowledge Management Program as a Part of Effective Integrated Management System for the ETRR2 Complex (Journal of Nuclear Technology in Applied Science, 2020)
In the IAEA documentations focus on management, for example the recently issued IAEA Safety Requirements publication Leadership and Management for Safety (IAEA Safety Standards Series No. GSR Part 2), it is understood that the organization information and knowledge (both tacit and explicit) should be managed as a resource for effective implementation of the management system. Also, lack of a knowledge management program is one of the warning signs of a decline in safety culture. This paper focuses on enhancing the Knowledge Management performance as a main step to achieve the goal of applying the Integrated Management System to improve safety, operation efficiency and performance. The Egyptian Atomic Energy Authority (EAEA) is a governmental research Authority that owns the Egypt Second Research Reactor (ETRR 2) complex. This Complex contains three nuclear installations (ETRR2 Reactor, Fuel Manufacturing Pilot Plant-FMPP and Radioisotopes Production Facility-RPF) and Administrative and engineering building (headquarter of the complex), which have a fairly adequate knowledge base. The paper introduces a proposal of Knowledge Management Program design for the ETRR2 complex. The objective of the proposed plan is first to evaluate the existing Knowledge base and then implement effective Knowledge Management (KM) program in order to avoid risks to overall operations such as ‘Risk of Knowledge Loss’ and lower safety and productivity.
Keywords: Data; Information; Knowledge Management; Integrated Management System